Regulatory T Cells in Chronic Heart Failure - Lu, Yuzhi; Xia, Ni; Cheng, Xiang (Frontiers in Immunology, 2021)
Heart failure is a global health challenge because of its high hospitalization and mortality rates. Inflammation and immune dysfunction are involved in this disease. Regulatory T cells (Tregs), that have received attention recently owing to their unique tissue functions, participate in both immunoregulation and tissue repair in the pathophysiology of heart failure. They are beneficial in the early stage of heart injury by suppressing excessive inflammatory responses and promoting stable scar formation. However, in heart failure, Tregs changed their phenotypes and functions, and became an anti-angiogenic and pro-fibrotic cell type. In this review, we summarized the functions of Tregs in the process of heart failure firstly. Then, we focused on the regulating function of Tregs on immune cells (including macrophages, dendritic cells, T cells, and B cells) and parenchymal cells (including cardiomyocytes, fibroblasts, and endothelial cells). The development of next-generation sequencing and gene editing technologies make it possible for the immunotherapy of heart failure. So, prospective therapeutic approaches based on Tregs in heart failure were also evaluated finally.